2021
DOI: 10.1021/jacs.1c06689
|View full text |Cite
|
Sign up to set email alerts
|

An “All-in-One” Synthetic Strategy for Linear Metalla[4]Catenanes

Abstract: One fascinating and challenging synthetic target in the field of mechanically interlocked molecules is the family of linear [4]­catenanes, which are topologically identical to the logo of automobile maker Audi. Herein, we report an “all-in-one” synthetic strategy for the synthesis of linear metalla­[n]­catenanes (n = 2–4) by the coordination-driven self-assembly of Cp*Rh-based (Cp* = η5-pentamethylcyclopentadienyl) organometallic rectangle π-donors and tetracationic organic cyclophane π-acceptors. We selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…50,51 A few other linear [4]-and [5] catenanes from either stepwise or one-pot synthesis have also been recently reported. [52][53][54][55] In 2017, Rowan and co-workers have explored the use of a metallopolymer to obtain [n]catenanes. 56 The metallopolymer consists of ditopic macrocycles and linear components coordinated via Zn 2+ ions in an alternate fashion, from which a mixture of branched, linear and cyclic [n]catenanes were obtained upon ring-closing metathesis (Fig.…”
Section: Increasing the Number Of Interlocked Componentsmentioning
confidence: 99%
“…50,51 A few other linear [4]-and [5] catenanes from either stepwise or one-pot synthesis have also been recently reported. [52][53][54][55] In 2017, Rowan and co-workers have explored the use of a metallopolymer to obtain [n]catenanes. 56 The metallopolymer consists of ditopic macrocycles and linear components coordinated via Zn 2+ ions in an alternate fashion, from which a mixture of branched, linear and cyclic [n]catenanes were obtained upon ring-closing metathesis (Fig.…”
Section: Increasing the Number Of Interlocked Componentsmentioning
confidence: 99%
“…In the exploration of synthetic strategies to construct supramolecular assemblies, half-sandwich rhodium-based organometallic fragments have shown distinct advantages in synthesizing a range of metallarectangles with adjustable sizes and diverse functional groups. 15–17 Herein, we designed and synthesized rhodium-based photoactive metallarectangles bearing 2,6- and 2,7- AD s, respectively. In general, dipolar repulsions of substituted anthracenes favor antiparallel isomers.…”
Section: Introductionmentioning
confidence: 99%
“…34,35 The group of Jin has reported the selective construction of a series of intricate structures, such as molecular Borromean ring assemblies, [44][45][46][47][48][49][50][51] Solomon links, [52][53][54] 3 1 , 55 double trefoil, 56 and 4 1 knots, 57 and [2,3,4]catenanes. 24,58 The topological transformations between these structures were explored in detail through concentration-, solvent-and hostguest chemistry effects or via the chemical reactivity of the metal ions and organic ligands. 47,59 Aer careful analysis of the structural characteristics of these supramolecular topologies, we have found that although a number of different forces, such as hydrogen bonding interactions, 57 hydrophobic effects, and others, 49 play diverse roles in the formation of these complexes, the decisive factor in the generation of these structures is generally p-p stacking interactions.…”
Section: Introductionmentioning
confidence: 99%